A comprehensive review on two-stage integrative schemes for the valorization of dark fermentative effluents. (18th August 2018) - Sivagurunathan, Periyasamy; Kuppam, Chandrasekhar; Mudhoo, Ackmez; Saratale, Ganesh D.; Kadier, Abudukeremu; Zhen, Guangyin; Chatellard, Lucile; Trably, Eric; Kumar, Gopalakrishnan
Abstract: This review provides the alternative routes towards the valorization of dark H2 fermentation effluents that are mainly rich in volatile fatty acids such as acetate and butyrate. Various enhancement and alternative routes such as photo fermentation, anaerobic digestion, utilization of microbial electrochemical systems, and algal system towards the generation of bioenergy and electricity and also for efficient organic matter utilization are highlighted. What is more, various integration schemes and two-stage fermentation for the possible scale up are reviewed. Moreover, recent progress for enhanced performance towards waste stabilization and overall utilization of useful and higher COD present in the organic source into value-added products are extensively discussed.